Infortunios de Alonso Ramirez : By Carlos de Siguenza y Gongora - Buscaglia-Salgado, José F. (Rutgers University Press, 2018)
Buscaglia is the first scholar to furnish direct and irrefutable proof that the story contained in the Infortunios/Misfortunes was based on the life and times of a man certifiably named Alonso Ramírez. This Rutgers edition is the most complete and authoritative bilingual edition of a work that grants us privileged access to the intricacies of early American subjectivity.